Literasi Finansial sebagai Konten Layanan Bimbingan bagi Mahasiswa - Aisha Nadya; Achmad Ali Syaifudin; Ahmad Rofi Suryahadikusumah (Prophetic : Professional, Empathy, Islamic Counseling Journal, 2024)
Financial literacy for students is needed so that they can recognize their own consumption patterns, make rational considerations, and control excessive consumption patterns. Currently, financial literacy is a life skill that must be possessed to support personal well-being. The lack of guidance and counseling research in this area encourages researchers to examine aspects of financial literacy needed by students (P1), and guidance strategies that can be used to strengthen students' financial literacy (P2). The method used is Systematic Literature Review (SLR) and uses the PRISMA model. The screening results showed nine publications indexed by scopus, that could be used as research data. The results of the Co-occurrence analysis show that there are four guidance contents related to financial literacy a) psychological aspects in financial decisions, b) short-term goal setting, c) financial decision making, and d) effective behavior in managing finances. The strategy used is a group strategy and a cognitive-based strategies. Guidance services can be strengthened by presenting visual data and strengthening personal goals in managing finances.